Moralischer Stress bei Medizinstudierenden und ärztlichen Berufseinsteigenden: Forschungsdesiderate im Rahmen der COVID-19-Pandemie - Kühlmeyer, Katja (Bundesgesundheitsblatt Gesundheitsforschung Gesundheitsschutz, 2020)
BACKGROUND: The COVID-19 pandemic poses particular challenges for people working in the medical sector. Some of the medical students and young medical professionals who are starting their work in healthcare facilities during this time are confronted with extraordinary moral challenges. A portion of them does not yet have sufficient coping skills to adequately deal with these challenges. This can lead to so-called moral distress (MoD). Permanent or intensive exposure to MoD can have serious consequences. Appropriate support services have the potential to improve the handling of MoD. OBJECTIVE: This article aims to provide an overview of the current state of research on MoD among medical students and young medical professionals in order to sensitize lecturers with responsibility for education and training and doctors in leading positions to the problem. MAIN PART: This article presents the scientific concept of MoD, known triggers, and options for prevention and intervention. The topic is presented with reference to the changes in patient care in the context of the COVID-19 pandemic and research needs are presented. CONCLUSION: The article illustrates the necessity of a German-language, interdisciplinary discourse on MoD among medical students and young professionals.